Research Status and Development Trend of KOA Population Rehabilitation Robots - Liu Kan; Wang Xupeng; Ji Xiaomin; Tang Xinyao; Han Bing (Jixie chuandong)
With the acceleration of the aging society, the incidence of knee osteoarthritis (KOA) tends to be younger, which brings great trouble to the society and patients. In order to effectively inhibit KOA lesions and assist KOA rehabilitation after joint replacement, all kinds of sports braces and rehabilitation training devices are used. Among them, rehabilitation aids play an important role in the rehabilitation training of KOA people. In order to study the application of rehabilitation robots in the rehabilitation training of KOA people more comprehensively, this research systematically reviews the research status of robot structure control in rehabilitation training for people with lower limb movement disorders based on the analysis of the rehabilitation needs of KOA population at different stages of disease. The key technologies of rehabilitation robots for KOA people are analyzed as well, which provides a theoretical basis for the design of rehabilitation robots for KOA people in the future.